Orbitálne komplikácie zápalov prínosových dutín - Šuchaň, M; Horňák, M; Kaliarik, L; Krempaská, S; Koštialová, T; Kovaľ, J (Ceska a slovenska oftalmologie, 2014)
Orbital complications categorised by Chandler are emergency. They need early diagnosis and agresive treatment. Stage and origin of orbital complications are identified by rhinoendoscopy, ophtalmologic examination and CT of orbite and paranasal sinuses. Periorbital cellulitis and early stage of orbital cellulitis can be treated conservatively with i. v. antibiotics. Monitoring of laboratory parameters and ophtalmologic symptoms is mandatory. Lack of improvement or worsening of symptoms within 24-48 hours and advanced stages of orbital complications are indicated for surgery. The purpose of the study is to evaluate epidemiology, clinical features and management of sinogenic orbital complications. Retrospective data of 8 patients with suspicion of orbital complication admited to hospital from 2008 to 2013 were evaluated. Patients were analyzed in terms of gender, age, CT findings, microbiology, clinical features, stage and treatment. Male and female were afected in rate 1,66:1. Most of patients were young adult in 3rd. and 4th. decade of life (62,5 %). Acute and chronic sinusitis were cause of orbital complication in the same rate. The most common origin of orbital complication was ethmoiditis (62,5 %), than maxillary (25 %) and frontal (12,5 %) sinusitis. Polysinusitis with affection of ethmoidal, maxillary and frontal sinuses (75 %) was usual CT finding. Staphylococcus epidermidis and Staphylococcus aureus were etiological agens in half of cases. Periorbital oedema (100 %), proptosis, chemosis (50 %), diplopia and glaucoma (12,5 %) were observed. Based on examinations, diagnosis of periorbital oedema/preseptal cellulitis was made in 3 (37,5 %), orbital cellulitis in 3 (37,5 %) and subperiosteal abscess in 2 cases (25 %). All patients underwent combined therapy - i. v. antibiotics and surgery within 24 hours. Eradication of disease from ostiomeatal complex (OMC), drainage of affected sinuses and drainage of subperiosteal abscess were done via fuctional endonasal endoscopic surgery (FEES). In case of superior subperiosteal abscess, combined endonasal and external approach (external orbitotomy) was needed. Combined therapy facilitated quick improvement of local and systematic symptoms. Average time of hospitalisation was 7 days. Early diagnosis and agresive combined therapy prevent loss of vision and life threatening complications.
Keywords: Male; stafylokokové infekce; Female; mladý dospělý; Orbital Cellulitis; antibakteriální látky; Staphylococcal Infections; Young Adult; drenáž; oční infekce bakteriální; Endoscopy; Eye Infections, Bacterial; mužské pohlaví; ženské pohlaví; Adult; Staphylococcus; endoskopie; Sinusitis; Retrospective Studies; Abscess; retrospektivní studie; Tomography, X-Ray Computed; dospělí; počítačová rentgenová tomografie; lidé; absces; orbitocelulitida; Drainage; sinusitida; Humans; Anti-Bacterial Agents